Quality Control of The Manufacturing Process of Sweet Bread in PT XYZ Yogyakarta - Aryani, Ade Safitri; Sirajuddin, Muhammad Mar’ie (Journal of Agri-Food Science and Technology, 2021)
Quality control is essential in the production line to ensure the quality of the final product. The quality control team ensure the standard of the produced products. This research aims to explore the quality control process in the production of sweet bread in PT XYZ and to determine the major defect of the product. Data were collected through interviews and a literature study. Pareto chart, control chart, and Fishbone diagram were used to analyze the data. These methods identify the kind of defects in the product and understand the process of controlling product quality. The results show that the quality control process had been carried out. However, some product defects were found, such as burned bread (15%), leakage (15%), and sticking (13%). Defect products might be due to some kind of factors such as human error, method production, and the equipment and materials used.